2020
DOI: 10.1142/s021906132050021x
|View full text |Cite
|
Sign up to set email alerts
|

Turing degrees in Polish spaces and decomposability of Borel functions

Abstract: We give a partial answer to an important open problem in descriptive set theory, the Decomposability Conjecture for Borel functions on an analytic subset of a Polish space to a separable metrizable space. Our techniques employ deep results from effective descriptive set theory and recursion theory. In fact it is essential to extend several prominent results in recursion theory (e.g. the Shore-Slaman Join Theorem) to the setting of Polish spaces. As a by-product we give both positive and negative results on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…In particular, the theory of generalized Turing degrees has achieved great success. The researchers have found a number of unexpected applications of the notion of metric/topological Turing degrees: Day-Miller [6] explained the behavior of Levin's neutral measures in algorithmic randomness theory; Gregoriades-Kihara-Ng [9] gave a partial answer to the open problem on generalizing the Jayne-Rogers theorem in descriptive set theory; Kihara-Pauly [21] proved a result related to descriptive set theory, infinite dimensional topology, and Banach space theory; Andrews-Igusa-Miller-Soskova [1] showed that the PA degrees are first-order definable in the enumeration degrees; Kihara-Ng-Pauly [20] established a classification theory of the enumeration degrees; et cetera.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the theory of generalized Turing degrees has achieved great success. The researchers have found a number of unexpected applications of the notion of metric/topological Turing degrees: Day-Miller [6] explained the behavior of Levin's neutral measures in algorithmic randomness theory; Gregoriades-Kihara-Ng [9] gave a partial answer to the open problem on generalizing the Jayne-Rogers theorem in descriptive set theory; Kihara-Pauly [21] proved a result related to descriptive set theory, infinite dimensional topology, and Banach space theory; Andrews-Igusa-Miller-Soskova [1] showed that the PA degrees are first-order definable in the enumeration degrees; Kihara-Ng-Pauly [20] established a classification theory of the enumeration degrees; et cetera.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the partition of X in Definition 10 can even be chosen to be Π 0 2 . Intricate arguments from descriptive set theory [13,33,38] then show that for Polish spaces, σ-homeomorphism agrees with second-level Borel isomorphism. Jayne had explored second-level Borel isomorphism of Polish spaces in 1974 [20] motivated by applications in Banach space theory.…”
Section: σ-Homeomorphismsmentioning
confidence: 98%
“…These hybrid difference operators seem relevant for studying σ-continuous functions (ω-decomposable functions; see e.g. [12]). As in Propositions 2.2 and 2.3, the classes…”
Section: Approximation With Mind-changesmentioning
confidence: 99%